ESTIMATES OF GENETIC EFFECTS FOR PHYSIOLOGICAL AND YIELD RELATED TRAITS IN MAIZE UNDER HIGH TEMPERATURE - H. M. W. Ali; A. Qayyum; M. A. Saleem; F. M. Wattoo; S. Saleem (Journal of Animal and Plant Sciences, 2022)
Abrupt climate changes and harsh environmental conditions are basic causes of food threatening scenarios in the world. Among these, global warming is proving as a major factor in declining of cereal production especially maize all around the world. Basic aim of this research was to observe the inheritance pattern of various physiological and yield attributes in maize under stress and selection of parents for future breeding program. Six heat tolerant maize inbred lines were mated in full diallel combination. Parents along-with F1 progeny were sown in the field using Randomized Complete Block Design with three replications. Data of seven (7) parameters like ear leaf area, leaf osmotic potential, chlorophyll contents, canopy temperature depression, net photosynthetic rate, plant height and grain yield were estimated for parents and their cross combinations. Graphical expression and dominance ratio depicted preponderance of non-additive gene action for all parameters under both environmental conditions except for leaf osmotic potential under stress environment. Due to over-dominance nature of inheritance pattern, heterosis breeding is a suitable breeding strategy for improvement of studied parameters. Inbreds NCIL-10-5 & D-135 had maximal dominant genes for most of the physiological & yield attributes under heat stress. These inbred lines have a potential of sustainable performance under adverse environment and can be used to develop heat tolerant maize hybrids with sustainable yield.
Keywords: Canopy temperature depression; Hayman analysis; Leaf osmotic potential; Maize